IMPLEMENTASI OUTDOOR EDUCATION TERHADAP MOTIVASI BELAJAR PENDIDIKAN JASMANI - Vina Lailia Nurjanah; Nanang Mulyana (Journal of Physical Education and Sport Science, 2019)
This study aimed to determine the students' learning motivation at eleventh grade students of science in following the learning process of physical education with the implementation of outdoor education at the Senior High School plus NU Panguragan. This study used experimental method under quantitative approach and the technique of collecting data used questionnaire. The subject of the study was 30 students of science class in Senior High School plus NU Panguragan. Tha sampling technique used non probability sampling or totally sampling and the data was analyzed using quantitative data analysis in the form of normality test, homogenity test and hypotesis rest (T Test). The result of the study showed that the implementation of outdoor education can increase Students' motivation in learning physical education at Senior High School pkus NU Panguragan based on the result of normality test, homogenity test with the significance value > 0.05 and hypotesis test states that Ho is rejected and Ha is accepted.